Preparation method of environment-friendly printing wear-resistant drying improved water-based gloss oil
The preparation of putaway mutant structural emulsion by using seed emulsion semi-continuous polymerization method in aqueous varnish, and adding GO through graphene oxide GO composite and physical mixing technology methods, the problem of insufficient drying speed and wear resistance of water-based varnish is solved, significantly improved its performance, and met the requirements of cigarette box packaging and other applications.
Patent Information
- Application Number
- CN202411754521.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-04-18
AI Technical Summary
The existing water-based varnish oil has insufficient drying speed and wear resistance, which leads to the surface being easily worn and unable to be used normally in applications such as cigarette box packaging.
Semi-continuous polymerization of seed emulsion was used to prepare polyacrylate CGPA emulsion with a core-bottom mutant structure, and GO was added through graphene oxide GO composite and physical mixing technology, and finally the additive ratio was adjusted to prepare aqueous varnish with improved wear resistance and dryness.
It significantly improves the dryness and wear resistance of water-based varnish, making it more stable in applications such as cigarette box packaging and meets printing requirements.
Smart Images

Figure CN119842286A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a method for preparing a water-based varnish for printing, and in particular to a method for preparing a water-based varnish for environmentally friendly printing with improved wear resistance and drying properties, belonging to the technical field of varnish for packaging printing. Background Art
[0002] Printing varnish is a common coating applied on the surface of printed matter to protect it from moisture, corrosion and wear, and to improve the gloss and make the color of the object more vivid. Currently, there are three main types of printing varnish, namely water-based varnish, traditional solvent-based varnish and UV-curable varnish.
[0003] Green printing is a printing method that uses green and environmentally friendly materials throughout the printing process, uses less energy, emits less or even zero harmful substances, and is harmless to the environment and humans. At the same time, the waste generated during production can be recycled and reused, or the printed products can be naturally degraded. Green printing is truly reflected in all aspects of the printing process, such as pre-press CTP plate making, water-based ink for printing, water-based varnish for post-press, and recycling of waste generated.
[0004] Post-press varnishing is a widely used link in post-press processing. Its function is to achieve the purpose of finishing and protecting printed products by applying varnish on them. However, many companies currently use oily varnish, whose main solvent is toxic and volatile toluene. Toluene not only causes air pollution, but also poses a serious threat to human physical and mental health. It can cause cancer and change the blood system and respiratory system when it enters the human body. It can be imagined that traditional oily oil does not meet the requirements of green printing, especially for the health and safety requirements of printing and packaging such as medical, food, and children's toys.
[0005] Water-based varnish is a green and environmentally friendly material with zero VOC emissions and no toxic gas emissions during use, which is in line with people's environmental protection concept. However, water-based varnish also has some disadvantages, such as slow drying speed and insufficient wear resistance. This is because water-based varnish uses water as the main solvent, and the latent heat of evaporation of water is higher. Compared with other solvents, it evaporates more slowly under the same conditions. During use, the film layer will be dry on the outside and wet on the inside, thereby reducing the wear resistance of the water-based varnish. In the actual production of enterprises, the problem is more prominent. After investigation, it is found that the insufficient drying makes the surface of the cigarette box susceptible to wear during the packaging process, resulting in the product being unable to be used normally. Therefore, these disadvantages restrict the wider application of water-based varnish.
[0006] Solving the disadvantages of poor drying properties and insufficient wear resistance of water-based varnish is a key link in promoting the development of water-based varnish. It is also an important step in the greening of printing. It is very necessary and has practical significance.
[0007] The problems that need to be solved in the preparation of printing water-based varnish in the prior art and the key technical difficulties of this application include:
[0008] (1) At present, many enterprises use oily varnishes, whose main solvent is toxic and volatile toluene. Toluene not only causes air pollution, but also poses a serious threat to human physical and mental health. It can cause cancer and change the blood system and respiratory system when it enters the human body. The oily oil in the prior art does not meet the requirements of green printing, especially the health and safety requirements for printing and packaging of medical, food, children's toys, etc. The water-based varnish in the prior art also has some disadvantages, such as slow drying speed and insufficient wear resistance. This is because water-based varnish uses water as the main solvent, and the latent heat of evaporation of water is higher. Compared with other solvents under the same conditions, it evaporates more slowly. During use, the film layer will be dry outside and wet inside, thereby reducing the wear resistance of the water-based varnish. In actual production, the problem is more prominent. The insufficient drying makes the surface of the cigarette box packaging process susceptible to wear, resulting in the product being unable to be used normally. These disadvantages restrict the wider application of water-based varnish.
[0009] (2) Currently, there is a need for more environmentally friendly printing methods and printing materials. Glazing, as a very important post-printing processing technology, has a finishing and protective effect on printed products, but traditional solvent-based varnishes and UV varnishes will volatilize more VOCs. Water-based varnish is a green and environmentally friendly varnish with water-based materials as solvents, but compared with the latter two, it has the disadvantages of insufficient wear resistance and poor drying properties. It is urgent to prepare a water-based printing varnish with good wear resistance, excellent drying properties, and suitable for printing and glazing. However, the existing technology lacks formulas and research conditions for emulsion polymerization, lacks soft and hard monomers and ratios, functional monomers, initiators, solvents and other raw material solutions that match the system, and does not master the polymerization temperature and emulsifier dosage. There is a lack of research on the reasonable ratio of the components of water-based varnish from the perspective of printability. There is a lack of ideal addition methods and addition amounts of graphene oxide, and the existing water-based varnish characterization, hardness evaluation, wear resistance evaluation, color evaluation, etc. are not highly evaluated.
[0010] (3) The typical commercial water-based varnishes in the current packaging field have problems such as insufficient wear resistance and drying speed that cannot meet product quality requirements. There is a lack of a series of solutions designed and evaluated to add different amounts of GO to water-based varnishes in different ways. It is impossible to prepare a water-based varnish with significantly improved wear resistance, greatly improved drying properties and good printability. First, there is a lack of a preparation method for core-shell variant polyacrylate CGPA emulsion: the monomer polymerization reaction is insufficient and the core-shell variant structure particle size does not meet the requirements; second, there is a lack of a preparation method for the composite materials GO-TMP and GO-CGPA; third, there is a lack of a preparation method for water-based acrylic resin varnishes. The water-based varnishes prepared by the existing technology have poor drying properties and no significant improvement in wear resistance, and all aspects of performance cannot meet printing requirements. Summary of the invention
[0011] The present application is firstly the preparation of core-shell variant structure polyacrylate CGPA emulsion, secondly the preparation of composite materials GO-TMP and GO-CGPA, and thirdly the preparation of water-based acrylic resin varnish. The best scheme is designed as follows: firstly compound GO with the cross-linking agent TMP, and use the composite GO-TMP as a cross-linking agent, wherein the GO content is 0.03% of the total mass of the varnish. Compared with the water-based varnish currently used by the enterprise, the varnish prepared by this scheme has greatly improved drying properties and significantly improved wear resistance, and all aspects of performance meet the printing requirements. The water-based varnish prepared in this application is a green and environmentally friendly varnish with hydrophilic materials as solvents. It has the advantages of being non-toxic, odorless, and free of VOC emissions during the application process, which is unmatched by traditional solvent-based varnishes and UV-curing varnishes. At the same time, it has the unique advantages of good wear resistance, excellent drying properties, and suitable for printing varnishing.
[0012] In order to achieve the above technical effects, the technical solutions adopted in this application are as follows:
[0013] A method for preparing an environmentally friendly printing water-based varnish with improved wear resistance and drying properties, firstly, a polyacrylate CGPA emulsion with core-shell variant structure latex particles is prepared by a seed emulsion semi-continuous polymerization method, then GO is added by means of a technical method of graphene oxide GO composite and physical mixing of the main components of the varnish, and finally, the ratio of the auxiliary agent is adjusted to prepare a water-based varnish with improved wear resistance and drying properties;
[0014] The preparation of core-shell variant polyacrylate CGPA emulsion includes the preparation of high glass transition temperature varnish and the preparation of core-shell variant emulsion. The appearance of CGPA emulsion and whether powdering occurs during coating are taken as the main indicators. It is determined that when the amount of emulsifier is 0.8% of the mass of the reaction monomer, the appearance of the emulsion is milky white with light blue fluorescence, and there is no powdering after coating and drying; it is determined that when the polymerization temperature is 80 to 85°C, each monomer is fully reacted, the core-shell variant particle size meets the requirements and there is no agglomeration, and the prepared CGPA emulsion contains the core-shell variant structure. Latex particles; the polyacrylate emulsion content of the compounded water-based varnish is 70%, and the GO-modified CGPA emulsion adopts three technical routes: the first is to physically add GO dispersion directly to the PA emulsion for physical blending; the second is to compound GO with the crosslinking agent trimethylolpropane TMP; the third is to copolymerize GO with each monomer during the preparation of the CGPA emulsion, wherein GO is compounded with the crosslinking agent TMP, and the composite GO-TMP is used as a crosslinking agent, and the GO content is 0.03% of the total mass of the varnish as the optimal solution;
[0015] 1) Preparation of core-shell variant polyacrylate CGPA emulsion: The CGPA emulsion was prepared by core-shell emulsion polymerization semi-continuous method, and the latex particles in the CGPA emulsion had a core-shell variant structure;
[0016] 2) Preparation of composite materials GO-TMP and GO-CGPA: GO and TMP react at 80°C under the catalytic conditions of FeCl3·6H2O to form a chemical bond between the two; during the preparation of CGPA, GO is added to the shell emulsion, GO reacts with the acrylate monomer, that is, a chemical bond is formed between them, and GO forms a network structure between the shell-core variant structure latex particles;
[0017] 3) Preparation of water-based acrylic resin varnish: CGPA emulsion is compounded into water-based varnish, and the mass proportions of the components of the water-based varnish are determined as follows: PA emulsion content is 70%, water-based acrylic resin content is 10%, solvent content is 12, auxiliary agent content is 5%, and cross-linking agent content is 3%.
[0018] Preferably, the high glass transition temperature varnish is prepared by using St and MMA as hard monomers to give the polymer film a certain hardness, and selecting BA as a soft monomer to give the film layer a certain flexibility and glossiness;
[0019] The Tg of each reactive monomer. When the monomers react with each other to form a polymer, the Tg of the polymer changes. A preliminary evaluation of the Tg is made. The preliminary estimation formula is as follows:
[0020]
[0021] Among them, W i is the mass fraction of the comonomer i, Tg i is the glass transition temperature of the comonomer i, which is an absolute temperature, Tg is the glass transition temperature of the random copolymer, which is an absolute temperature;
[0022] The mass ratio of BA, St, MMA and AA is 35:32:3:1, the core-shell mass ratio is 3:2, and the mass of the initiator is 0.5% of the total mass of the reaction monomers BA, St, MMA and AA.
[0023] Preferably, the core-shell variant structure emulsion is prepared by:
[0024] The first step is to prepare the pre-emulsion: weigh appropriate amounts of deionized water, SDS, core layer monomers BA, MMA, and St, and then place them in a 40°C water bath for ultrasonic dispersion for 30 min;
[0025] The second step is to prepare the seed emulsion and polymerize: weigh appropriate amounts of deionized water and APS, stir and dissolve them thoroughly, and heat them to 80°C in an oil bath; separate 10% of the pre-emulsion and slowly add it to the base material within 15 minutes, and keep the temperature at 80°C for 15 minutes after the addition to fully react; add APS to the remaining 90% of the emulsion and add it to the base material within 1 hour, and keep the temperature for reaction for 30 minutes after the addition;
[0026] The third step is to prepare the shell emulsion and polymerize it: weigh appropriate amounts of deionized water, shell monomers BA, MMA, St, AA, SDS, and APS, and then place them in a 40°C water bath for ultrasonic dispersion for 30 min;
[0027] The fourth step is to prepare the copolymer emulsion: in an 80°C oil bath, slowly add the shell emulsion into the seed emulsion prepared in the second step within 1 hour. After the addition, maintain the temperature at 80°C for 30 minutes for sufficient reaction, cool to 30°C, and then adjust the pH value to 8-9 with ammonia water to obtain a PA emulsion with a core-shell variant structure.
[0028] Preferably, the preparation of the modified graphene oxide composite crosslinking agent: composite graphene oxide (GO) and trimethylolpropane (TMP) to improve the heat absorption performance of TMP and improve the crosslinking speed and effect of TMP;
[0029] Graphene oxide is obtained by oxidation of graphite, and contains more hydroxyl and carboxyl active functional groups on the surface. Graphene oxide has relatively better dispersion performance in water and solvents, and is easier to react chemically with other substances. The modified graphene oxide crosslinker is a polyol, which reacts with the carboxyl groups on graphene oxide under certain temperature and catalyst conditions.
[0030] Preparation process of modified graphene oxide crosslinker: take a certain amount of TMP, add it to a certain amount of GO dispersion, stir to make the two fully dispersed, take a certain amount of catalyst FeCl3·6H2O and add it to the mixed solution and stir; put the mixed solution into an 80℃ oil bath, and then stir it at a certain speed for 30min; after the reaction is completed, take a certain amount of 732 cation exchange resin and add it to the mixed solution, let it stand for 1h to remove Fe 3+ .
[0031] Preferably, graphene oxide dispersed composite polyacrylate is prepared by utilizing the active functional groups (such as hydroxyl groups) contained in GO to react with the carboxyl groups on the acrylic acid monomer to achieve the characteristics of GO's high thermal effect and network structure, and the GO dispersion is first mixed with the shell emulsion and then added dropwise;
[0032] The specific steps for preparing graphene oxide dispersed composite polyacrylate are as follows:
[0033] Step 1, prepare the pre-emulsion: weigh appropriate amounts of deionized water, SDS, core layer monomers BA, MMA, and St, and then place them in a 40°C water bath for ultrasonic dispersion for 30 min;
[0034] Step 2, prepare seed emulsion and polymerize: weigh appropriate amount of deionized water and APS, stir and dissolve them thoroughly, and heat them to 80°C in an oil bath; separate 10% of the pre-emulsion and slowly add it to the base material within 15 minutes, and keep the temperature at 80°C for 15 minutes after the addition to fully react; add APS to the remaining 90% of the emulsion and add it to the base material within 1 hour, and keep the temperature for reaction for 30 minutes after the addition;
[0035] Step 3, prepare shell emulsion and polymerize: weigh appropriate amount of deionized water, shell monomers BA, MMA, St, AA, SDS, APS and appropriate amount of GO dispersion, and then place in a 40 °C water bath for ultrasonic dispersion for 30 min;
[0036] Step 4, prepare copolymer emulsion: in an 80°C oil bath, slowly add the shell emulsion into the seed emulsion prepared in step 2 within 1 hour. After the addition, maintain the temperature at 80°C for 30 minutes for sufficient reaction, cool to 30°C, and then adjust the pH value to 8 to 9 with ammonia water to obtain a GO-PA emulsion with a core-shell variant structure.
[0037] Preferably, the main agent and solvent of water-based acrylic resin varnish: the main agent of water-based varnish is CGPA emulsion and water-based acrylic resin. The water-soluble acrylic resin has good gloss and dispersibility, good wear resistance, fast drying and transparency. The solvent of water-based varnish is mainly water, which has the function of good solubility and dispersibility of auxiliary agents and various additives, and determines the viscosity of glass paint. In addition to water, a certain amount of anhydrous ethanol is added as a solvent to reduce the surface tension of the varnish and increase the drying speed.
[0038] Preferably, the additives of water-based acrylic resin varnish are:
[0039] (1) Leveling agent: Use 3020 water-based silicone coating, with the addition amount being 1% of the total amount, to improve the leveling property of the emulsion and the smoothness of the film layer;
[0040] (2) Thickener: Hydroxyethyl cellulose is used, and the addition amount is 0.5% of the total amount to achieve a suitable viscosity and improve the viscosity of the emulsion;
[0041] (3) Defoamer: SL defoamer 4 # , the dosage is 0.5%, which reduces the foam in the system and eliminates the bubbles in the emulsion;
[0042] (4) Plasticizer: Ethylene glycol is used in an amount of 1% of the total amount to make the varnish film layer have better physical and mechanical properties;
[0043] (5) Film-forming agent: 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate is used, with an addition amount of 2%, to accommodate or bond other components in the water-based varnish to form a film, and firmly bond the film to the substrate.
[0044] Preferably, the water-based varnish compounding process: compounding varnish on the basis of preparing core-shell variant structure polyacrylate CGPA emulsion, modified graphene oxide composite crosslinking agent, and graphene oxide dispersed composite polyacrylate, and establishing three preparation methods of water-based varnish according to the addition method of GO;
[0045] Compounding method: Add the solvent, additive and cross-linking agent to the CGPA emulsion in a certain proportion, and fully disperse them by physical stirring to obtain a water-based varnish with performance that meets the requirements;
[0046] (1) After CGPA emulsion and GO dispersion were physically mixed (PA+GO), solvents and additives were added to prepare varnish. During the preparation process, water-based acrylic resin was added during the preparation of PA emulsion, and the content was 10% of the total mass of water-based varnish;
[0047] (2) GO (GO-PA) is added during the preparation of CGPA to form a chemical bond between GO and acrylic resin monomers, and then a suitable amount of solvents and additives are added to prepare a water-based varnish. During the preparation process, water-based acrylic resin is also added during the preparation of CGPA emulsion, and the content is 10% of the total mass of the water-based varnish; at the same time, GO is added to the shell emulsion during the preparation of CGPA emulsion, so that GO is formed in the shell structure of the shell-core variant structure, and GO is used to improve the thermal effect of the modified material and its network structure;
[0048] (3) GO is first compounded with the crosslinker TMP (GO-TMP), and the composite GO-TMP is used as a crosslinker for standby use and added before the varnish is used. During the preparation process, the water-based acrylic resin is added during the preparation of the CGPA emulsion, and the content is 10% of the total mass of the water-based varnish. The acrylic resin is added to the core-shell variant structure emulsion according to the core-shell mass ratio, and the prepared GO-TMP is added before the varnish is used.
[0049] Preferably, the influence model of the content of water-based acrylic resin on glossiness and hygroscopicity is as follows: a water-soluble acrylic resin with low relative molecular weight is added during the emulsion polymerization process to improve the glossiness, adhesion and wear resistance of the varnish film layer, and the amount of water-based acrylic resin is reduced under the condition that the glossiness and wear resistance of the varnish meet the requirements;
[0050] When the amount of water-soluble resin is between 0 and 10%, the glossiness increases with the increase of resin content. The viscosity of the water-soluble resin itself is large and its particle size is small. As the amount of water-soluble resin increases, the viscosity of the system increases. At the same time, the amount of small particle size substances in the system increases, the smoothness of the film layer increases, and the glossiness increases. When the water-soluble resin is added to a certain extent, the glossiness of the film layer tends to decrease. The solid content of a 50% aqueous solution of the water-soluble resin is low. When the amount is too large, the overall solid content of the system is small. When the solid content is less than a certain level, the glossiness of the film layer is eventually reduced. The appropriate resin content is 10%.
[0051] Preferably, the influence model of GO addition mode and content on the wear resistance of water-based varnish film is as follows:
[0052] Qualitative analysis: With the increase of GO content in water-based varnish, the wear resistance gradually increases. The wear resistance of varnish is higher than that of varnish without GO. At the same time, when the GO content is in the range of 0.01 to 0.05%, the GO content is positively correlated with the wear resistance. The CGPA+GO-TMP type varnish has the highest overall wear resistance, followed by the GO-CGPA+TMP type varnish, and the CGPA+GO+TMP type varnish has the lowest overall wear resistance.
[0053] Compared with the prior art, the innovations and advantages of this application are:
[0054] (1) This application proposes, designs and evaluates a series of solutions for adding different amounts of GO to water-based varnishes in different ways to address the problems that typical commercial water-based varnishes in the current packaging field have insufficient wear resistance and a drying speed that cannot meet product quality requirements. First, the formulation and emulsion polymerization conditions are designed, and appropriate soft and hard monomers and their ratios, functional monomers, initiators, solvents and other raw materials that match the system are selected, and a suitable experimental plan is designed. Polymerization temperature and emulsifier dosage are two of the more important factors in the preparation of acrylic resin emulsions, and the ideal ranges of the two are studied. Second, the reasonable ratio of the components of water-based varnish is studied from the perspective of printability. When the polyacrylic resin emulsion is well prepared, water-based varnishes with good printability are prepared by adjusting different amounts of water-based resins and other additives, and the reasonable ratio of the components is obtained. Third, the ideal addition method and amount of graphene oxide were studied. Experimental schemes with different addition methods and different contents of GO were designed for adding GO to water-based varnish. The better scheme was obtained by characterizing the prepared water-based varnish, evaluating hardness, abrasion resistance, and color. After coating, drying, and performance evaluation, the best scheme was selected by comparing with the varnish currently used by the company and different formulations. Finally, a water-based varnish with significantly improved abrasion resistance, greatly improved drying, and good printing suitability was prepared.
[0055] (2) The present application is firstly the preparation of core-shell variant structure polyacrylate CGPA emulsion, secondly the preparation of composite materials GO-TMP and GO-CGPA, and thirdly the preparation of water-based acrylic resin varnish. The optimal scheme is designed as follows: firstly compound GO with the crosslinking agent TMP, and use the composite GO-TMP as a crosslinking agent, wherein the GO content is 0.03% of the total mass of the varnish. Compared with the water-based varnish currently used by the enterprise, the varnish prepared by this scheme has greatly improved drying properties and significantly improved wear resistance, and all aspects of performance meet the printing requirements. The water-based varnish prepared in this application is a green and environmentally friendly varnish with hydrophilic materials as solvents. It has the advantages of being non-toxic, odorless, and free of VOC emissions during the application process, which is unmatched by traditional solvent-based varnishes and UV-curing varnishes. At the same time, it has the unique advantages of good wear resistance, excellent drying properties, and suitable for printing varnishing.
[0056] (3) The present application first adopts a seed emulsion semi-continuous polymerization method to prepare a polyacrylate CGPA emulsion having a core-shell variant structure latex particle, then adds Go by means of a technical means of graphene oxide GO compounding and physical mixing of the main components of the varnish, and finally adjusts the ratio of the auxiliary agent to prepare a water-based varnish with improved wear resistance and drying properties; the preparation of the core-shell variant structure polyacrylate CGPA emulsion includes the preparation of a high glass transition temperature varnish and the preparation of a core-shell variant structure emulsion, with the appearance of the CGPA emulsion and whether powdering occurs during coating as the main indicators; the compounded water-based varnish has a polyacrylate emulsion content of 70%, a water-based acrylic resin content of 10%, a solvent content of 12%, an auxiliary content of 5%, and a cross-linking agent content of 3%; the GO-modified CGPA emulsion is prepared by compounding GO with TMP and then adding it to the water-based varnish, and the optimal solution is when the GO content is 0.03%. The evaluation and comprehensive analysis of the performance of water-based varnishes show that the water-based acrylic resin varnish developed in the present application achieves the expected purpose and has good abrasion resistance while meeting the basic printability of the varnish. BRIEF DESCRIPTION OF THE DRAWINGS
[0057] Figure 1 It is a schematic diagram of the glass transition temperature of the components related to the preparation of nuclear variant structure emulsion.
[0058] Figure 2 This is a schematic diagram of the polymerization reaction between MMA, BA and AA.
[0059] Figure 3 This is a schematic diagram of the polymerization reaction of St itself.
[0060] Figure 4 This is the infrared spectrum of CGPA emulsion prepared by core variation structure process.
[0061] Figure 5 It is a schematic diagram of latex particles with core-shell variant structures in CGPA emulsion.
[0062] Figure 6 This is a diagram of the esterification reaction between the modified graphene oxide crosslinker and the carboxyl groups on graphene oxide.
[0063] Figure 7 This is a schematic diagram of the preparation process of CGPA+GO water-based varnish.
[0064] Figure 8 This is a schematic diagram of the preparation process of GO-CGPA+TMP water-based varnish.
[0065] Fig. 9 This is a comparison chart of the drying test of different series of water-based varnishes.
[0066] Fig.10 This is a comparison chart of the wear resistance test of different series of water-based varnish films.
[0067] Fig.11 This is a test analysis chart using unprinted ink paper as the experimental material.
[0068] Fig.12 This is a test analysis chart using printed red ink paper as experimental material.
[0069] Fig.13 This is an analysis chart of the effect of GO addition method and content on the properties of varnish. DETAILED DESCRIPTION
[0070] The following is a further description of the technical solution of the method for preparing the environmentally friendly printing wear-resistant and drying improved water-based varnish provided by the present application in conjunction with the accompanying drawings, so that those skilled in the art can better understand the present application and implement it.
[0071] Water-based varnish is a green and environmentally friendly varnish with hydrophilic materials as solvents. It has the advantages of being non-toxic, odorless, and free of VOC emissions during the application process, which is unmatched by traditional solvent-based varnishes and UV-curing varnishes. However, compared with the latter two, it has the disadvantages of poor drying properties and insufficient wear resistance. These two properties are particularly important for water-based varnishes and are key factors in determining whether the varnish can be used normally. In order to solve the current problem of insufficient drying properties and wear resistance of water-based varnishes, this application first adopts a seed emulsion semi-continuous polymerization method to prepare a polyacrylate CGPA emulsion with core-shell variant structure latex particles, and then adds Go through the technical means of graphene oxide GO composite and physical mixing of the main components of the varnish, and finally adjusts the ratio of the additives to prepare a water-based varnish with improved wear resistance and drying properties;
[0072] The preparation of core-shell variant polyacrylate CGPA emulsion includes the preparation of high glass transition temperature varnish and core-shell variant emulsion. The appearance of CGPA emulsion and whether powdering occurs during coating are taken as the main indicators. It is determined that when the amount of emulsifier is 0.8% of the mass of the reaction monomer, the appearance of the emulsion is milky white with light blue fluorescence, and there is no powdering after coating and drying; it is determined that when the polymerization temperature is 80 to 85°C, each monomer is fully reacted, and the prepared CGPA emulsion contains core-shell variant latex particles;
[0073] The compounded water-based varnish contains 70% polyacrylate emulsion, 10% water-based acrylic resin, 12% solvent, 5% auxiliary agent and 3% cross-linking agent.
[0074] GO-modified CGPA emulsion adopts three technical routes: the first is to directly add GO dispersion into PA emulsion for physical blending; the second is to compound GO with cross-linking agent trimethylolpropane TMP; the third is to copolymerize GO with various monomers during the preparation of CGPA emulsion, among which GO is compounded with TMP and then added to water-based varnish, and the optimal solution is when the GO content is 0.03%.
[0075] The evaluation and comprehensive analysis of the performance of water-based varnish show that the water-based acrylic resin varnish developed in this application achieves the expected purpose and has good abrasion resistance while meeting the basic printability of the varnish.
[0076] 1. Preparation of core-shell polyacrylate CGPA emulsion
[0077] (I) Preparation of high glass transition temperature varnish
[0078] The glass transition temperature of random polyacrylate emulsion polymer (referring to two or more irregularly distributed polymers in the repeating unit structure) is 30°C. Because the low glass transition temperature will lead to low coating hardness and low wear resistance, it is easy to stick to the board during polishing, and the paper will also easily stick to each other after drying. If the glass temperature is too high, it will lead to poor film formation, weak film layer, and poor folding resistance.
[0079] St and MMA are used as hard monomers to give the polymer film a certain hardness, and BA is selected as a soft monomer to give the film a certain flexibility and glossiness. Their glass transition temperatures are as follows: Figure 1 shown.
[0080] The Tg of each reactive monomer. When the monomers react with each other to form a polymer, the Tg of the polymer changes. A preliminary evaluation of the Tg is made. The preliminary estimation formula is as follows:
[0081]
[0082] Among them, Wi is the mass fraction of the comonomer i, Tg i is the glass transition temperature of the copolymerized monomer i, which is an absolute temperature; Tg is the glass transition temperature of the random copolymer, which is an absolute temperature.
[0083] The mass ratio of BA, St, MMA and AA is 35:32:3:1, the core-shell mass ratio is 3:2, and the mass of the initiator is 0.5% of the total mass of the reaction monomers BA, St, MMA and AA.
[0084] In the process of emulsion polymerization, the seed emulsion first polymerizes to produce the microsphere core structure, and then the shell monomer is added to form the shell structure. At the same time, the reaction monomers on the core and shell are not only individual reactions, but also polymerization reactions of two or more monomers. Figure 2 It is the polymerization reaction between MMA, BA and AA. Figure 3 It is a polymerization reaction of St itself.
[0085] (II) Preparation of core-shell variant structure emulsion
[0086] The first step is to prepare the pre-emulsion: weigh appropriate amounts of deionized water, SDS, core layer monomers BA, MMA, and St, and then place them in a 40°C water bath for ultrasonic dispersion for 30 min;
[0087] The second step is to prepare the seed emulsion and polymerize: weigh appropriate amounts of deionized water and APS, stir and dissolve them thoroughly, and heat them to 80°C in an oil bath; separate 10% of the pre-emulsion and slowly add it to the base material within 15 minutes, and keep the temperature at 80°C for 15 minutes after the addition to fully react; add APS to the remaining 90% of the emulsion and add it to the base material within 1 hour, and keep the temperature for reaction for 30 minutes after the addition;
[0088] The third step is to prepare the shell emulsion and polymerize it: weigh appropriate amounts of deionized water, shell monomers BA, MMA, St, AA, SDS, and APS, and then place them in a 40°C water bath for ultrasonic dispersion for 30 min;
[0089] The fourth step is to prepare the copolymer emulsion: in an 80°C oil bath, slowly add the shell emulsion into the seed emulsion prepared in the second step within 1 hour. After the addition, maintain the temperature at 80°C for 30 minutes for sufficient reaction, cool to 30°C, and then adjust the pH value to 8-9 with ammonia water to obtain a PA emulsion with a core-shell variant structure.
[0090] (III) Emulsion evaluation and characterization
[0091] 1. Infrared spectrum analysis
[0092] Take a certain amount of sample latex film and use the evaluation instrument to evaluate the reflection infrared spectrum of the film layer. Figure 4 Medium, 3084cm -1 、3062cm -1 、3026cm -1 The sharp band at 1602cm is caused by the stretching vibration of =CH of benzene ring; -1 、1493cm -1 、1451cm -1 The benzene ring C=C skeleton stretching vibration absorption peak is at 761cm -1 、701cm -1 The out-of-plane deformation vibration peak of monosubstituted benzene CH is at 3438cm -1 It is the stretching vibration absorption peak of hydroxyl (-OH); 2956cm -1 、2871cm -1 The methyl group (-CH 3 ) asymmetric and symmetric stretching vibration absorption peaks; 2928cm -1 It is a methylene group (-CH 2 ) asymmetric stretching vibration absorption peak; 1732cm -1 It is the typical stretching vibration absorption peak of carbonyl C=O in AA, BA and MMA; 1636cm' is the stretching vibration absorption peak of CC; 1164cm -1 、1123cm -1 The asymmetric stretching vibration absorption peak of the ester group is 1068 cm -1 The peak of CC skeleton vibration is at 990cm -1 、965cm -1 、908cm -1 The peaks at the bottom are the characteristic peaks of the out-of-plane bending vibration of CH connected to C=C. The appearance of these characteristic peaks indicates that AA, BA and MMA participate in the reaction.
[0093] 2. Transmission Electron Microscope Analysis
[0094] In order to observe whether the CGPA emulsion prepared in the present application contains latex particles with shell-core variant structure, the latex particles were magnified and observed using a transmission electron microscope to 100 nm. Figure 5 shown.
[0095] Take a certain amount of sample and dilute it until it is transparent and clear, and use a JEM-2100 (HR) transmission electron microscope to magnify and observe the latex particles. The evaluation voltage is 200kV, and the material of the electron gun is LaB6. Most of the latex particles are spherical, uniform in size, and have good dispersibility. At the same time, the particle size of the core-shell particles is significantly larger than that of the core layer particles, indicating that the polymerization of the second monomer does occur on the surface of the seed microspheres. According to the magnification ratio and the measured size, the size of the core-shell variant structure particles is estimated, the average particle size of the core layer particles is about 85nm, and the average particle size of the core-shell particles is about 100nm. The TEM evaluation and observation results show that the PA latex latex particles prepared in this application have formed a core-shell variant structure.
[0096] (IV) Model of influencing factors in emulsion preparation process
[0097] 1. Model of the effect of emulsifier content on emulsion
[0098] The finishing and protective effects of varnish do not allow the emulsion to be significantly powdered after film coating. An appropriate amount of emulsifier allows the acrylate monomer to be better dispersed and fully reacted, but if the emulsifier is excessive, it will not only cause the emulsion film to have a higher hydrophilicity, but also cause the emulsion to powder after coating. Therefore, the emulsifier content in the preparation process of the emulsion should be appropriate. The mass ratio of BA, St, MMA, and AA in this application is 35:32:3:1, and the core-shell mass ratio is 3:2.
[0099] When the emulsifier content is 0.5% to 0.8% of the reaction monomer content, after the emulsifier is increased, the coagulation phenomenon is reduced, and there is no powdering after coating. This phenomenon is due to the fact that when the emulsifier disperses the monomer in water, the monomer is dispersed into small droplets, and the emulsifier molecules are wrapped on the surface of these small droplets. Therefore, the greater the amount used, the more complete the wrapping and the higher the stability; but when the emulsifier content is 0.8% to 2.0% of the reaction monomer content, after the emulsifier is increased, the coagulation phenomenon gradually increases, and the powdering after coating gradually becomes serious. This is because when the emulsifier is used in excess, the droplet size formed is too small, and its interfacial energy is large, which leads to a decrease in the stability of the emulsion, thereby causing the phenomenon of coagulation. At the same time, the droplet size is too small and it will be slightly transparent. Too high an emulsifier content will also cause the emulsifier to precipitate after the coating is dried, resulting in powdering. Therefore, according to the above analysis, it is best when the emulsifier amount accounts for 0.8% of the reaction monomer content.
[0100] 2. Model of the effect of emulsion polymerization temperature on emulsion
[0101] The emulsion polymerization temperature affects whether the polymerization reaction can proceed normally and the quality of the polymerization product. The polymerization temperature of this application is 70 to 90°C, the mass ratio of BA, St, MMA, and AA is 35:32:3:1, the core-shell mass ratio is 3:2, and the amount of emulsifier is 0.8% of the mass of the reaction monomer. Different polymerization temperatures are used to observe their effects on the appearance and coagulation of the emulsion.
[0102] (1) Effect of polymerization temperature on emulsion particle size
[0103] When the polymerization temperature is between 70 and 85°C, the color of the emulsion gradually shows blue light. When the blue light of the styrene acrylic emulsion is strong, the corresponding emulsion particle size is approximately between 100nm and 50nm. Below 50nm, the whiteness of the emulsion decreases significantly and it becomes a little clear, that is, it tends to be slightly transparent. The blue light decreases. When the emulsion is greater than 100nm, it is bright white with very high whiteness. As the particle size increases, the blue light gradually disappears. The particle size at which the blue light disappears is around 500 to 1000nm. When the emulsion is at a polymerization temperature between 70 and 75°C, the emulsion particle size is greater than 1000nm, at 80 to 85°C, the emulsion particle size is between 50 and 1000nm, and at 85 to 90°C, the emulsion particle size is greater than 1000nm. However, the emulsion has already coagulated at this time, indicating that the emulsion particles have exceeded the usable range.
[0104] In the emulsion polymerization of core-shell variant structure emulsion, the diameter of latex particles is an important indicator to characterize the polymer emulsion. The styrene-acrylic emulsion prepared with styrene, acrylate and acrylic acid as the main monomers has a latex particle size between 100 and 500nm. The coating with this as the main film-forming material is non-toxic and non-polluting.
[0105] Therefore, based on the application of styrene acrylic emulsion in compounding water-based varnish, the polymerization temperature is controlled at 80 to 85°C.
[0106] (2) Relationship model between polymerization temperature and emulsion taste
[0107] When the temperature is 70 to 75°C, the emulsion has a pungent smell and there are oily substances on the surface. This is because the emulsion contains residual monomers that did not participate in the reaction. When the polymerization temperature is low, the free radical concentration is small, and the initiation rate of the initiator is low, which reduces the diffusion rate of free radicals from the water phase to the latex particles, resulting in insufficient monomer reaction and residues. The emulsion has a pungent smell and oily substances on the surface; when the temperature is 90°C, the emulsion condenses. This is because the temperature is too high, causing the degree of polymerization of the monomers in the emulsion to be too high, resulting in condensation.
[0108] Combining the above two aspects, when the polymerization temperature is 80 to 85°C, the monomer reaction is sufficient and appropriate, and the latex particle size meets the use requirements.
[0109] 2. Preparation of modified graphene oxide composite cross-linking agent
[0110] Composite graphene oxide (GO) and trimethylolpropane (TMP) improves the heat absorption performance of TMP and increases the cross-linking speed and effect of TMP.
[0111] Graphene oxide is obtained by oxidation of graphite. It contains more hydroxyl and carboxyl active functional groups on the surface. Graphene oxide has better dispersion performance in water and solvents and is easier to react chemically with other substances. The modified graphene oxide crosslinker is a polyol. Under certain temperature and catalyst conditions, it undergoes esterification reaction with the carboxyl groups on graphene oxide. The reaction principle is as follows: Figure 6 shown.
[0112] Preparation process of modified graphene oxide crosslinker: take a certain amount of TMP, add it to a certain amount of GO dispersion, stir to make the two fully dispersed, take a certain amount of catalyst FeCl3·6H2O and add it to the mixed solution and stir; put the mixed solution into an 80℃ oil bath, and then stir it at a certain speed for 30min; after the reaction is completed, take a certain amount of 732 cation exchange resin and add it to the mixed solution, let it stand for 1h to remove Fe 3+ .
[0113] 3. Preparation of graphene oxide dispersed composite polyacrylate
[0114] The active functional groups (such as hydroxyl groups) contained in GO are used to react with the carboxyl groups on the acrylic monomer to achieve the characteristics of GO's high thermal effect and network structure. The GO dispersion is first mixed with the shell emulsion and then added dropwise.
[0115] The specific steps for preparing graphene oxide dispersed composite polyacrylate are as follows:
[0116] Step 1, prepare the pre-emulsion: weigh appropriate amounts of deionized water, SDS, core layer monomers BA, MMA, and St, and then place them in a 40°C water bath for ultrasonic dispersion for 30 min;
[0117] Step 2, prepare seed emulsion and polymerize: weigh appropriate amount of deionized water and APS, stir and dissolve them thoroughly, and heat them to 80°C in an oil bath; separate 10% of the pre-emulsion and slowly add it to the base material within 15 minutes, and keep the temperature at 80°C for 15 minutes after the addition to fully react; add APS to the remaining 90% of the emulsion and add it to the base material within 1 hour, and keep the temperature for reaction for 30 minutes after the addition;
[0118] Step 3, prepare shell emulsion and polymerize: weigh appropriate amount of deionized water, shell monomers BA, MMA, St, AA, SDS, APS and appropriate amount of GO dispersion, and then place in a 40 °C water bath for ultrasonic dispersion for 30 min;
[0119] Step 4, prepare copolymer emulsion: in an 80°C oil bath, slowly add the shell emulsion into the seed emulsion prepared in step 2 within 1 hour. After the addition, maintain the temperature at 80°C for 30 minutes for sufficient reaction, cool to 30°C, and then adjust the pH value to 8 to 9 with ammonia water to obtain a GO-PA emulsion with a core-shell variant structure.
[0120] 4. Preparation of water-based acrylic resin varnish
[0121] CGPA emulsion is the main component of acrylic ester water-based varnish, but not the only component. The physical properties and printability of CGPA emulsion cannot meet the production requirements. It is necessary to add a certain amount of water-based acrylic resin and various additives to improve the various properties of CGPA emulsion.
[0122] (I) Components and compounding methods of water-based acrylic resin varnish
[0123] 1. Main agent and solvent
[0124] The main agents of water-based varnish are CGPA emulsion and water-based acrylic resin. Water-soluble acrylic resin has good gloss and dispersibility, good wear resistance, fast drying and transparency. The solvent of water-based varnish is mainly water, which has the function of good solubility and dispersibility of auxiliary agents and various additives, and determines the viscosity of glass paint. In addition to water, a certain amount of anhydrous ethanol is added as a solvent to reduce the surface tension of the varnish and increase the drying speed.
[0125] 2. Additives
[0126] (1) Leveling agent: Use 3020 water-based silicone coating, with the addition amount being 1% of the total amount, to improve the leveling property of the emulsion and the smoothness of the film layer;
[0127] (2) Thickener: Hydroxyethyl cellulose is used, and the addition amount is 0.5% of the total amount to achieve a suitable viscosity and improve the viscosity of the emulsion;
[0128] (3) Defoamer: SL defoamer 4 # , the dosage is 0.5%. Reduce the foam in the system and eliminate the bubbles in the emulsion;
[0129] (4) Plasticizer: Ethylene glycol is used in an amount of 1% of the total amount to make the varnish film layer have better physical and mechanical properties.
[0130] (5) Film-forming agent: 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate is used, with an addition amount of 2%, to accommodate or bond other components in the water-based varnish to form a film, and firmly bond the film to the substrate.
[0131] 3. Water-based varnish compounding process
[0132] Varnish was compounded based on the preparation of core-shell variant structure polyacrylate CGPA emulsion, modified graphene oxide composite crosslinker and graphene oxide dispersed composite polyacrylate. Three preparation methods of water-based varnish were established according to the adding method of GO.
[0133] Compounding method: Add the solvent, additive and cross-linking agent to the CGPA emulsion in a certain proportion, and fully disperse them by physical stirring to obtain a water-based varnish with performance that meets the requirements;
[0134] (1) After CGPA emulsion and GO dispersion are physically mixed (PA+GO), solvents and additives are added to prepare varnish. The preparation process is as follows: Figure 7 As shown. During the preparation process, water-based acrylic resin is added during the preparation of PA emulsion, and the content is 10% of the total mass of water-based varnish;
[0135] (2) GO (GO-PA) is added during the preparation of CGPA to form a chemical bond between GO and acrylic resin monomers, and then a suitable amount of solvent and additives are added to prepare a water-based varnish. The preparation process is as follows: Figure 8 As shown. During the preparation process, water-based acrylic resin is also added during the preparation of CGPA emulsion, and the content is 10% of the total mass of water-based varnish; at the same time, GO is added to the shell emulsion during the preparation of CGPA emulsion, so that GO is formed in the shell structure of the shell-core variant structure, and GO is used to improve the thermal effect of the modified material and its network structure;
[0136] (3) GO is first compounded with the crosslinker TMP (GO-TMP), and the composite GO-TMP is used as a crosslinker for standby use and added before the varnish is used. During the preparation process, the water-based acrylic resin is added during the preparation of the CGPA emulsion, and the content is 10% of the total mass of the water-based varnish. The acrylic resin is added to the core-shell variant structure emulsion according to the core-shell mass ratio, and the prepared GO-TMP is added before the varnish is used.
[0137] 2. Impact Factor Analysis Model
[0138] 1. Model of the effect of water-based acrylic resin content on gloss and hygroscopicity
[0139] Adding a water-soluble acrylic resin with a low relative molecular weight (average molecular weight 5000) during the emulsion polymerization process can improve the gloss, adhesion and wear resistance of the varnish film, but the acrylic resin will increase the hydrophilicity of the coating, and excessive use will cause serious water absorption in the varnished printed matter. Therefore, under the condition that the gloss and wear resistance of the varnish meet the requirements, the amount of water-based acrylic resin should be reduced.
[0140] Water-based varnish was prepared with resin content of 0%, 10%, 20%, 30%, and 40% as gradients for coating, drying, evaluation, analysis, and screening. When the amount of water-soluble resin was between 0 and 10%, the glossiness increased with the increase of resin content. The viscosity of the water-soluble resin itself was large, and its particle size was small. With the increase of the amount of water-soluble resin, the viscosity of the system increased. At the same time, the small particle size substances in the system increased, and the smoothness and glossiness of the film layer increased. When the water-soluble resin was added to a certain extent, the glossiness of the film layer tended to decrease. The solid content of the 50% aqueous solution of the water-soluble resin was low. When the amount was too large, the overall solid content of the system was small. When the solid content was less than a certain level, the glossiness of the film layer was finally reduced. Therefore, the more suitable resin content is 10%.
[0141] 2. Model of the effect of GO addition method and content on water-based varnish
[0142] Adding GO to water-based varnish will change the color of the varnish, and will also change other properties of the varnish, such as stability. The evaluation results show that the sample types CGPA+GO+TMP, GO-CGPA+TMP, and CGPA+GO-TMP are water-based varnishes prepared by three different technical routes. Adding GO will change the color of the emulsion. As the content of GO increases, the color of the emulsion gradually deepens, from milky white to dark gray. The stability of the emulsion also decreases with the increase of GO content. After standing for 12 hours, all samples will not show condensation. After standing for 24 hours, the varnish containing GO will show different degrees of condensation, especially the CGPA+GO-TMP type varnish with a GO content of 0.03 to 0.05%. After standing for 48 hours, there will be different degrees of condensation, especially the CGPA+GO-TMP type varnish with a GO content of 0.04 to 0.05%. The condensation phenomenon is more serious. The addition of GO leads to a decrease in the stability of the varnish because GO has good thermal conductivity, which will accelerate the conjunctiva of the varnish, and condensation will occur. CGPA+GO-TMP type varnish contains GO-TMP. At the same time, TMP, as a cross-linking agent, has the function of promoting curing and drying and increasing the drying speed. If GO is compounded with it, TMP can absorb more energy under the same conditions, thereby increasing its activity and making the cross-linking effect more obvious. Therefore, the condensation phenomenon of CGPA+GO-TMP type varnish is more prominent.
[0143] 3. Model of the effect of GO addition method and content on the drying property of water-based varnish
[0144] Drying property is an extremely important property of water-based varnish. Drying property affects the film-forming speed and film performance of the varnish, and also affects the production efficiency. This application conducts drying property experiments on water-based varnishes with different technical routes and different GO contents. The experimental results are as follows: Fig. 9 shown.
[0145] Fig. 9 The sample types CGPA+GO+TMP, GO-CGPA+TMP, and CGPA+GO-TMP are water-based varnishes prepared by three different technical routes, and the drying temperature is 50°C. The water loss ratio is the ratio of the water loss weight to the weight before drying.
[0146] Within a constant drying time, the water loss ratio of all prepared varnish samples is higher than that of a certain varnish used in the enterprise production, indicating that the drying speed is higher than that of the varnish used by the enterprise. This is because GO has good thermal conductivity and can improve the heat absorption of water-based varnish under the same conditions, thereby increasing its film-forming drying speed. At the same time, with the increase of GO content in water-based varnish, the varnish prepared by the three technical routes all show a trend of gradually increasing water loss ratio, indicating that the drying speed gradually increases, indicating that the GO content is in the range of 0.01 to 0.05%, and its content is positively correlated with the drying speed of varnish. Then, the water loss ratio of the varnish prepared by the three technical routes is different. Among them, the CGPA+GO-TMP type varnish has the highest overall, followed by the CGPA+GO+TMP type varnish, and the GO-CGPA+TMP type varnish has the lowest overall, and the drying speed is also ranked in order, because TMP, as a cross-linking agent, itself has the function of promoting curing and drying and increasing the drying speed. If GO is compounded with it and added to the varnish, the effect is more obvious; the GO-CGPA+TMP type varnish has the slowest drying speed, because GO and the acrylic resin monomer undergo a full chemical reaction, and its thermal conductivity only acts on the acrylic monomer polymer, and does not act on the cross-linking agent TMP, resulting in the slowest drying speed. Finally, in the varnish prepared by the technical route GO-CGPA+TMP, the water loss ratio of the varnish with 0.01% and 0.02% GO content is the same as that of the varnish without GO, both of which are 0.19, because a small amount of GO does not play a significant role in improving thermal conductivity and promoting drying in this preparation route.
[0147] 4. Model of the effect of GO addition method and content on the hardness of water-based varnish film
[0148] After the varnish currently used by the company and the prepared water-based varnish were applied and dried, the hardness of the film layer was evaluated using a pencil hardness tester. From the evaluation results, it can be seen that the hardness of all evaluated varnish film layers is H, indicating that GO has no effect on the hardness of the varnish film layer, and the prepared varnish film layer has reached the hardness of the varnish film layer currently used by the company.
[0149] 5. Model of the effect of GO addition method and content on the wear resistance of water-based varnish film
[0150] Two methods are used to judge the wear resistance of each varnish sample film layer. One is qualitative judgment, that is, after the varnish is coated and dried, a wear test is carried out. After a certain number of frictions, the degree of wear of the sample is observed to judge the degree of wear resistance; the other is quantitative judgment, that is, after the wear test, the change in the color density value of the sample is evaluated to judge the degree of wear resistance.
[0151] (1) Qualitative analysis
[0152] With the increase of GO content in water-based varnish, the varnish prepared by the three technical routes all showed a trend of gradually improving wear resistance, and most of the varnishes had higher wear resistance than the varnish without GO, indicating that the addition of GO has a positive effect on the wear resistance of the varnish film. At the same time, when the GO content is in the range of 0.01 to 0.05%, the GO content is positively correlated with the wear resistance. Secondly, among the varnishes prepared by the three technical routes, 13 have reached or exceeded the wear resistance of the water-based varnish currently used by the enterprise, and 2 have not reached the wear resistance of the varnish currently used by the enterprise, which may be because the GO content is low and the effect of improving the wear resistance of the film layer is not more obvious. Finally, the CGPA+GO-TMP type varnish has the highest overall wear resistance, the GO-CGPA+TMP type varnish has the second highest wear resistance, and the CGPA+GO+TMP type varnish has the lowest overall wear resistance. According to several factors that affect wear resistance, it can be inferred that, under the same conditions of hardness, toughness, adhesion and surface friction coefficient, it may be because the CGPA+GO-TMP type varnish has the fastest drying speed and the highest degree of drying, which makes its film layer more firm and wear-resistant. The GO-CGPA+TMP type varnish film layer has a chemical bond formed between GO and the acrylic monomer polymer, and GO has a network structure, which makes the film layer microstructure more compact, so its wear resistance is higher.
[0153] (2) Quantitative analysis
[0154] The result of this application is Fig.10 As shown. With the increase of GO content in varnish, the varnish prepared by the three technical routes all showed a trend of gradually decreasing density value change rate before and after the friction test, and most of them were smaller than the density value change rate of the varnish used by the enterprise and the varnish without adding GO. The better the wear resistance of the varnish film layer, the smaller the density value change after coating, that is, the smaller the density change rate. Overall, adding GO improves the wear resistance of varnish, and when the GO content is in the range of 0.01 to 0.05%, its content is positively correlated with the wear resistance of varnish. Secondly, among all the samples, 2 did not reach the wear resistance of the varnish currently used by the enterprise, because the GO content was low, and the effect of improving the wear resistance of the film layer was not more obviously achieved. Finally, the CGPA+GO-TMP type varnish has the highest overall wear resistance, the GO-CGPA+TMP type varnish has the second highest wear resistance, and the CGPA+GO+TMP type varnish has the lowest overall wear resistance.
[0155] 6. Model of the effect of GO addition method and content on the color of printed products
[0156] The effect of the film layer on the color of printed products after adding different contents of GO to the varnish and drying it was studied, and the color difference was compared with the varnish currently used by the company and without adding GO. In order to make the results more accurate and reliable, this application uses two kinds of paper without printing ink (white cardboard) and printed red ink as materials.
[0157] (1) Using unprinted paper as the experimental material, the results are as follows Fig.11 shown.
[0158] Fig.11 △E1 represents the color difference between each sample after coating and the original paper, △E2 represents the color difference between each sample after coating and the sample after coating with varnish by the enterprise, and the chromaticity value of the original paper is: L=102.67, a=1.4, b=2.05.
[0159] Depend on Fig.11 It can be seen that the varnish used by the enterprise and the varnish prepared by the enterprise will affect the color presentation of the printed product, and the color difference produced by the varnish prepared by the three technical routes is greater than the color difference produced by the varnish used by the enterprise and the varnish without adding GO. This is because the added GO is bright yellow, which causes the varnish to have color. Secondly, in the prepared varnish, the color difference increases with the increase of GO content. When the GO content is in the range of 0.01 to 0.05%, the GO content is positively correlated with the color difference.
[0160] (2) Using red ink printed paper as the experimental material, the experimental results are as follows Fig.12 shown.
[0161] Depend on Fig.12 It can be seen that the varnish used by the enterprise and the varnish prepared by the enterprise will affect the color presentation of the printed product, and the color difference produced by the varnish prepared by the three technical routes is greater than the color difference produced by the varnish used by the enterprise and the varnish without adding GO. This is because the added GO is bright yellow, which causes the varnish to have color. Secondly, in the prepared varnish, the color difference increases with the increase of GO content. It can be seen that when the GO content is in the range of 0.01 to 0.05%, the GO content is positively correlated with the color difference.
[0162] The color difference of the prepared varnish after coating on the white sample should not be greater than 2.0, and the color difference after coating on the magenta sample should not be greater than 3.5. Through the above analysis of the effects of GO addition method and amount on the appearance, stability, drying, hardness, abrasion resistance and color presentation of printed products, it can be seen that GO has improved the drying and abrasion resistance, but has a negative effect on the stability and color presentation of printed products. Therefore, the best technical route and optimal content should be selected based on the effects of GO on various properties. The effects of GO addition method and amount on the various properties of varnish are as follows Fig.13 shown.
[0163] Fig.13 In the subjective judgment, A represents no wear, B represents slight wear, C represents obvious wear, and D represents severe wear: △E1 represents the color difference between white cardboard after coating with various types of varnish and before coating, and △E2 represents the color difference between printed red ink paper after coating with various types of varnish and before coating.
[0164] Selection method: water loss ratio, hardness, subjective observation wear resistance and GO content are positively correlated, density change, color difference and GO content are negatively correlated; water loss ratio, hardness, subjective observation wear resistance are selected at a high level, density change is selected at a low level, △E1 and △E2 cannot exceed 1.5, and the lower the better. After comprehensive comparison, the best technical route and formula are finally selected: CGPA+GO-TMP technical route is selected, GO content is 0.03%, and resin content is 10%. Compared with the varnish currently used by the company, the varnish prepared by this scheme has greatly improved drying properties, a higher improvement in wear resistance, no difference in film hardness, and the color difference caused to the printed product is within an acceptable range.
Claims
1. A method for preparing an environmentally friendly printing wear-resistant and drying improved water-based varnish, characterized in that: Firstly, the polyacrylate CGPA emulsion with core-shell variant structure latex particles was prepared by seed emulsion semi-continuous polymerization method, then graphene oxide GO was added by means of graphene oxide GO composite and physical mixing of the main components of varnish, and finally the proportion of additives was adjusted to prepare a water-based varnish with improved wear resistance and drying properties. The preparation of core-shell variant polyacrylate CGPA emulsion includes the preparation of high glass transition temperature varnish and the preparation of core-shell variant emulsion. The appearance of CGPA emulsion and whether powdering occurs during coating are taken as the main indicators. It is determined that when the amount of emulsifier is 0.8% of the mass of the reaction monomer, the appearance of the emulsion is milky white with light blue fluorescence, and there is no powdering after coating and drying; it is determined that when the polymerization temperature is 80 to 85°C, each monomer is fully reacted, the core-shell variant particle size meets the requirements and there is no agglomeration, and the prepared CGPA emulsion contains the core-shell variant structure. Latex particles; the polyacrylate emulsion content of the compounded water-based varnish is 70%, and the GO-modified CGPA emulsion adopts three technical routes: the first is to physically add GO dispersion directly to the PA emulsion for physical blending; the second is to compound GO with the crosslinking agent trimethylolpropane TMP; the third is to copolymerize GO with each monomer during the preparation of the CGPA emulsion, wherein GO is compounded with the crosslinking agent TMP, and the composite GO-TMP is used as a crosslinking agent, and the GO content is 0.03% of the total mass of the varnish as the optimal solution; 1) Preparation of core-shell variant polyacrylate CGPA emulsion: The CGPA emulsion was prepared by core-shell emulsion polymerization semi-continuous method, and the latex particles in the CGPA emulsion had a core-shell variant structure; 2) Preparation of composite materials GO-TMP and GO-CGPA: GO and TMP react at 80°C under the catalytic conditions of FeCl3·6H2O to form a chemical bond between the two; during the preparation of CGPA, GO is added to the shell emulsion, GO reacts with the acrylate monomer, that is, a chemical bond is formed between them, and GO forms a network structure between the shell-core variant structure latex particles; 3) Preparation of water-based acrylic resin varnish: CGPA emulsion is compounded into water-based varnish, and the mass proportions of the components of the water-based varnish are determined as follows: PA emulsion content is 70%, water-based acrylic resin content is 10%, solvent content is 12, auxiliary agent content is 5%, and cross-linking agent content is 3%.
2. The method for preparing the environmentally friendly printing wear-resistant and drying improved water-based varnish according to claim 1, characterized in that: Preparation of high glass transition temperature varnish: St and MMA are used as hard monomers to give the polymer film a certain hardness, and BA is selected as a soft monomer to give the film layer a certain flexibility and glossiness; The Tg of each reactive monomer. When the monomers react with each other to form a polymer, the Tg of the polymer changes. A preliminary evaluation of the Tg is made. The preliminary estimation formula is as follows: Among them, W i is the mass fraction of the comonomer i, Tg i is the glass transition temperature of the comonomer i, which is an absolute temperature, Tg is the glass transition temperature of the random copolymer, which is an absolute temperature; The mass ratio of BA, St, MMA and AA is 35:32:3:1, the core-shell mass ratio is 3:2, and the mass of the initiator is 0.5% of the total mass of the reaction monomers BA, St, MMA and AA.
3. The method for preparing the environmentally friendly printing wear-resistant and drying improved water-based varnish according to claim 1, characterized in that: Preparation of core-shell variant structure emulsion: The first step is to prepare the pre-emulsion: weigh appropriate amounts of deionized water, SDS, core layer monomers BA, MMA, and St, and then place them in a 40°C water bath for ultrasonic dispersion for 30 min; The second step is to prepare the seed emulsion and polymerize: weigh appropriate amounts of deionized water and APS, stir and dissolve them thoroughly, and heat them to 80°C in an oil bath; separate 10% of the pre-emulsion and slowly add it to the base material within 15 minutes, and keep the temperature at 80°C for 15 minutes after the addition to fully react; add APS to the remaining 90% of the emulsion and add it to the base material within 1 hour, and keep the temperature for reaction for 30 minutes after the addition; The third step is to prepare the shell emulsion and polymerize it: weigh appropriate amounts of deionized water, shell monomers BA, MMA, St, AA, SDS, and APS, and then place them in a 40°C water bath for ultrasonic dispersion for 30 min; The fourth step is to prepare the copolymer emulsion: in an 80°C oil bath, slowly add the shell emulsion into the seed emulsion prepared in the second step within 1 hour. After the addition, maintain the temperature at 80°C for 30 minutes for sufficient reaction, cool to 30°C, and then adjust the pH value to 8-9 with ammonia water to obtain a PA emulsion with a core-shell variant structure.
4. The method for preparing the environmentally friendly printing wear-resistant and drying improved water-based varnish according to claim 1, characterized in that: Preparation of modified graphene oxide composite crosslinking agent: Graphene oxide (GO) and trimethylolpropane (TMP) are composited to improve the heat absorption performance of TMP and increase the crosslinking speed and effect of TMP; Graphene oxide is obtained by oxidation of graphite, and contains more hydroxyl and carboxyl active functional groups on the surface. Graphene oxide has relatively better dispersion performance in water and solvents, and is easier to react chemically with other substances. The modified graphene oxide crosslinker is a polyol, which reacts with the carboxyl groups on graphene oxide under certain temperature and catalyst conditions. Preparation process of modified graphene oxide crosslinker: take a certain amount of TMP, add it to a certain amount of GO dispersion, stir to make the two fully dispersed, take a certain amount of catalyst FeCl3·6H2O and add it to the mixed solution and stir; put the mixed solution into an 80℃ oil bath, and then stir it at a certain speed for 30min; after the reaction is completed, take a certain amount of 732 cation exchange resin and add it to the mixed solution, let it stand for 1h to remove Fe 3+ .
5. The method for preparing the environmentally friendly printing wear-resistant and drying improved water-based varnish according to claim 1, characterized in that: Preparation of graphene oxide dispersed composite polyacrylate: The active functional groups (such as hydroxyl groups) contained in GO are used to react with the carboxyl groups on the acrylic acid monomer to achieve the characteristics of GO's high thermal effect and network structure. The GO dispersion is first mixed with the shell emulsion and then added dropwise; The specific steps for preparing graphene oxide dispersed composite polyacrylate are as follows: Step 1, prepare the pre-emulsion: weigh appropriate amounts of deionized water, SDS, core layer monomers BA, MMA, and St, and then place them in a 40°C water bath for ultrasonic dispersion for 30 min; Step 2, prepare seed emulsion and polymerize: weigh appropriate amount of deionized water and APS, stir and dissolve them thoroughly, and heat them to 80°C in an oil bath; separate 10% of the pre-emulsion and slowly add it to the base material within 15 minutes, and keep the temperature at 80°C for 15 minutes after the addition to fully react; add APS to the remaining 90% of the emulsion and add it to the base material within 1 hour, and keep the temperature for reaction for 30 minutes after the addition; Step 3, prepare shell emulsion and polymerize: weigh appropriate amount of deionized water, shell monomers BA, MMA, St, AA, SDS, APS and appropriate amount of GO dispersion, and then place in a 40 °C water bath for ultrasonic dispersion for 30 min; Step 4, prepare copolymer emulsion: in an 80°C oil bath, slowly add the shell emulsion into the seed emulsion prepared in step 2 within 1 hour. After the addition, maintain the temperature at 80°C for 30 minutes for sufficient reaction, cool to 30°C, and then adjust the pH value to 8 to 9 with ammonia water to obtain a GO-PA emulsion with a core-shell variant structure.
6. The method for preparing the environmentally friendly printing wear-resistant and drying improved water-based varnish according to claim 1, characterized in that: The main agent and solvent of water-based acrylic resin varnish: The main agent of water-based varnish is CGPA emulsion and water-based acrylic resin. Water-soluble acrylic resin has good gloss and dispersibility, good wear resistance, fast drying and transparency. The solvent of water-based varnish is mainly water, which has the function of good solubility and dispersibility of auxiliary agents and various additives, and determines the viscosity of glass paint. In addition to water, a certain amount of anhydrous ethanol is added as a solvent to reduce the surface tension of the varnish and increase the drying speed.
7. The method for preparing the environmentally friendly printing wear-resistant and drying improved water-based varnish according to claim 1, characterized in that: Additives for water-based acrylic resin varnish: (1) Leveling agent: Use 3020 water-based silicone coating, with the addition amount being 1% of the total amount, to improve the leveling property of the emulsion and the smoothness of the film layer; (2) Thickener: Hydroxyethyl cellulose is used, and the addition amount is 0.5% of the total amount to achieve a suitable viscosity and improve the viscosity of the emulsion; (3) Defoamer: SL defoamer 4 # , the dosage is 0.5%, which reduces the foam in the system and eliminates the bubbles in the emulsion; (4) Plasticizer: Ethylene glycol is used in an amount of 1% of the total amount to make the varnish film layer have better physical and mechanical properties; (5) Film-forming agent: 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate is used, with an addition amount of 2%, to accommodate or bond other components in the water-based varnish to form a film, and firmly bond the film to the substrate.
8. The method for preparing the environmentally friendly printing wear-resistant and drying improved water-based varnish according to claim 1, characterized in that: Water-based varnish compounding process: compound varnish based on the preparation of core-shell variant structure polyacrylate CGPA emulsion, modified graphene oxide composite crosslinker, and graphene oxide dispersed composite polyacrylate, and establish three preparation methods of water-based varnish according to the addition method of GO; Compounding method: Add the solvent, additive and cross-linking agent to the CGPA emulsion in a certain proportion, and fully disperse them by physical stirring to obtain a water-based varnish with performance that meets the requirements; (1) After CGPA emulsion and GO dispersion were physically mixed (PA+GO), solvents and additives were added to prepare varnish. During the preparation process, water-based acrylic resin was added during the preparation of PA emulsion, and the content was 10% of the total mass of water-based varnish; (2) GO (GO-PA) is added during the preparation of CGPA to form a chemical bond between GO and acrylic resin monomers, and then a suitable amount of solvents and additives are added to prepare a water-based varnish. During the preparation process, water-based acrylic resin is also added during the preparation of CGPA emulsion, and the content is 10% of the total mass of the water-based varnish; at the same time, GO is added to the shell emulsion during the preparation of CGPA emulsion, so that GO is formed in the shell structure of the shell-core variant structure, and GO is used to improve the thermal effect of the modified material and its network structure; (3) GO is first compounded with the crosslinker TMP (GO-TMP), and the composite GO-TMP is used as a crosslinker for standby use and added before the varnish is used. During the preparation process, the water-based acrylic resin is added during the preparation of the CGPA emulsion, and the content is 10% of the total mass of the water-based varnish. The acrylic resin is added to the core-shell variant structure emulsion according to the core-shell mass ratio, and the prepared GO-TMP is added before the varnish is used.
9. The method for preparing the environmentally friendly printing wear-resistant and drying improved water-based varnish according to claim 1, characterized in that: The influence model of the content of water-based acrylic resin on gloss and hygroscopicity: adding a water-soluble acrylic resin with low relative molecular weight during the emulsion polymerization process improves the gloss, adhesion and wear resistance of the varnish film. When the gloss and wear resistance of the varnish meet the requirements, the amount of water-based acrylic resin is reduced; When the amount of water-soluble resin is between 0 and 10%, the glossiness increases with the increase of resin content. The viscosity of the water-soluble resin itself is large and its particle size is small. As the amount of water-soluble resin increases, the viscosity of the system increases. At the same time, the amount of small particle size substances in the system increases, the smoothness of the film layer increases, and the glossiness increases. When the water-soluble resin is added to a certain extent, the glossiness of the film layer tends to decrease. The solid content of a 50% aqueous solution of the water-soluble resin is low. When the amount is too large, the overall solid content of the system is small. When the solid content is less than a certain level, the glossiness of the film layer is eventually reduced. The appropriate resin content is 10%.
10. The method for preparing environmentally friendly printing wear-resistant and drying improved water-based varnish according to claim 1, characterized in that: Model of the effect of GO addition method and content on the wear resistance of water-based varnish film: Qualitative analysis: With the increase of GO content in water-based varnish, the wear resistance gradually increases. The wear resistance of varnish is higher than that of varnish without GO. At the same time, when the GO content is in the range of 0.01 to 0.05%, the GO content is positively correlated with the wear resistance. The CGPA+GO-TMP type varnish has the highest overall wear resistance, followed by the GO-CGPA+TMP type varnish, and the CGPA+GO+TMP type varnish has the lowest overall wear resistance.